THE IMPACT OF BULLYING BEHAVIOUR ON CHILDREN: A LITERATURE REVIEW - Dewi Hestiani K; Sudirman, Sudirman (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Bullying has become a worldwide social problem. Statistical data states that 3 out of 4 children in Indonesia have experienced some violence perpetrated by their peers. Bullying can be carried out by a person or group that is aggressive because of an imbalance of power between the groups involved, it can occur in the form of mocking, spreading false news, inciting, frightening or intimidating, isolating, threatening, bullying, yelling, and physically attacking such as slapping, pushing or hitting. Bullying behavior is a bad action that can have a negative impact and can trigger trauma to the victim so that it can hinder the next stage of development. This paper will contain the results of a literature review conducted on several previous studies on bullying behavior. It will focus on the discussion on the impact caused by bullying behavior on children.